Implementation of Science Curriculum in Nigerian Tertiary Education: Problems and Way Forward - Abiodun, Ayo, Victoria; Margaret, Ahmed, Foluke (International Journal on Integrated Education, 2023)
The paper examined the problems facing the implementation of science curriculum in the Nigerian tertiary institutions. Secondary data were used to support the points raised in the article. The secondary data were sourced from printed materials and online publications by recognized institutions and individual authors. The paper concludes that inadequate funds, shortage of science lecturers, lack of infrastructure facilities, corruption, strike actions, brain-drain and ineffective capacity building programme, insecurity challenges and poor supervision are problems facing the implementation of science curriculum in the Nigerian tertiary institutions. Based on this problems identified, the paper recommended adequate funding of tertiary institutions in Nigeria as means of ensuring effective science curriculum implementation in the institutions across the country.